The relationship between hand - eye dominance on the performance in target sports: A systematic review - Çil, E. T.; Koç, E. A.; Hürsan, B.; Cerbezer, N. (Clinical Case Reports International, 2023)
Any individual that exhibits physiologic superiority and priority, or preference behaviors in any bilateral structure is referred to as dominant. When thinking about the target sport in sports, hand and eye dominance might be a crucial performance factor. In this study, the association between performance in target sports and dominant eye and hand dominance is examined in order to determine whether visual dominance will be added as a new criterion for performance. Utilizing the terms archery, biathlon, shooting, dart and air-shooting as well as the keywords dominant eye, ocular dominance, dominant eye dominant hand laterality. The search was conducted in the databases "PubMed, Google Scholar, Elsevier ScienceDirect and Web of Science" on the online library pages of Yeditepe University.